Mendelian randomization analysis of the causal relationship between immune cells and keloid - Jingwen Zou; Pengkhun Nov; Kunpeng Du (PAGEPress Publications, 2024)
Immune cells play complex roles in the formation of keloid. We aimed to investigate the causal relationship between immune cells and keloid and provide genetic evidence for the association between immune cells and keloid risk. Based on data from GWAS, we performed a comprehensive two-sample Mendelian Randomization (MR) analysis of 731 immune cell traits in 481,912 keloid cases. We used Inverse-Variance Weighted (IVW) method as the primary analysis. Then, a comprehensive sensitivity analysis was adopted to verify the results' robustness, heterogeneity, and horizontal pleiotropy. Finally, reverse MR analysis was performed. The IVW method in forward MR analysis showed that CD66b++ myeloid cell AC was negatively associated with keloid risk (OR < 1, P < 0.05). Consistently, reverse MR analysis showed keloid risk was negatively associated with CD66b++ myeloid cell AC (OR = 0.85, P = 0.012). No significant horizontal pleiotropy or heterogeneity was observed. The results of MR analysis demonstrate a bidirectional causal association between CD66b++ myeloid cell AC and keloid formation, suggesting CD66b++ myeloid cell AC is a protective factor against keloid.